Physico-chemical characterization of PMsub(10) and PMsub(2.5) in the Belgrade urban area - Tasić, Mirjana (Acta chimica slovenica, 2006)
An extensive study on urban aerosols with the aim to determine the sources and provide a physico-chemical description of PM10 and PM2.5, present in the urban air of Belgrade, was performed. Daily aerosol samples were collected in four seasonal episodes at three representative places in the urban area of Belgrade in the period of 2002-2004. Suspended particles were sampled on pure Teflon filters by using a Mini-Vol air sampler (Airmetrics Co., Inc.; 5 L min-1 flow rate) and were analyzed by a JEOL JSM-5300 SEM via an energy dispersive X-ray microanalysis system (EDX). The airborne particulate matter was characterized from a physico-chemical point of view to supply information on the particle composition and the compounds carried on their surfaces. The combined use of microanalysis and statistical methods enabled identification of several groups of particles such as: soot, sulfates, Si-rich, metal-rich and biological particles.
Keywords: aerosoli; analizna kemija; ecology; ekologija; kemija okolja; mikroanaliza; zrak